Facile synthesis of electrocatalytically active bismuth oxide nanosheets for detection of palladium traces in pharmaceutical wastewater - Zhao, Ke (2022)
Current synthesis routes of bismuth oxide nanosheets (BiONS) are relatively complicated, requiring the use of halogens or metalloids. Herein, a facile method to synthesize BiONS without the addition of halogens or other metalloids was developed. The synthesized BiONS were identified to have flake-shaped structures (300-1000 nm in width) with the thickness of 6-10 nm, which were predominantly made of β-Bi2O3. Such BiONS were applied to modify the surface of screen-printed carbon electrodes (BiONS-SPCEs) for the development of a robust palladium (Pd2+) sensor. After optimizing the electrochemical parameters of the sensor, it was found that the linear sensor response range and limit of detection for Pd2+ were 40-400 and 1.4 ppb, respectively. The electrocatalytic activity of the Pd2+-sensor was validated in the competing environment of other metal and metalloid ions. Real samples collected during a Pd recovery process from pharmaceutical wastewater were used to verify the application of BiONS-SPCEs in control of palladium recovery process. The quantitative results of post recovery palladium concentrations obtained using BiONS-SPCEs in treated pharmaceutical wastewater samples were in good agreement with those obtained by inductively coupled plasma-optical emission spectrometry (ICP-OES). Thus, such Pd2+-sensor provided the possibility of on-site process control of complex industrial samples for obtaining near-instant information that would lead to better management of resources used in the process, and same time assure environmental standards for both recovered products and processed discharge.